Konseling Kontrasepsi Pada Masa Prenatal Dan Postnatal Terhadap Penggunaan Kontrasepsi Modern: Sistematik Literatur Review - Retno Heru Setyorini; Andina Vita Sutanto (Sekolah Tinggi Ilmu Kesehatan Akbidyo, 2021)
The prenatal and postnatal periods require contraceptive counseling to increase understanding of the benefits of contraception for reproductive health. The purpose of this literature review is to analyze the results of research related to the effectiveness of contraceptive counseling carried out in the prenatal and postnatal periods to increase the use of modern contraception. Writing this journal uses a literature study approach from several databases, namely PubMed, ProQuest and Google Scholar. Eight research journals reported that interventions in various forms and media led to better knowledge, more positive attitudes, and higher intentions towards contraceptive uptake. The results of the study can be used as a source of information to help solve health problems, especially regarding decision making using modern contraception.Keywords: Counseling, Family Planning, Contraception, Women of Childbearing Age